Benthic indices for trophic status - Kaushal, D K (Indian Journal of Fisheries, 2011)
An attempt has been made to enumerate benthic indicies and to establish thebehaviour of Gobindsagar reservior in terms of productivity. The delineation ofB 1 indicates that Gobindsagar is a weak eutrophic reservior